Rules or consequences? The role of ethical mindsets in moral dynamics - Gert Cornelissen
Recent research on the dynamics of moral behavior has documented two contrasting phenomena - moral consistency and moral balancing. Moral balancing refers to the phenomenon whereby behaving (un)ethically decreases the likelihood of doing so again at a later time. Moral consistency describes the opposite pattern - engaging in (un)ethical behavior increases the likelihood of doing so later on. Three studies support the hypothesis that individuals' ethical mindset (i.e., outcome-based versus rule-based) moderates the impact of an initial (un)ethical act on the likelihood of behaving ethically in a subsequent occasion. More specifically, an outcome-based mindset facilitates moral balancing and a rule-based mindset facilitates moral consistency.moral balancing, moral consistency, ethical mindsets, ethical behavior